Piraterie maritime: pas d’«internationalisation» de la fonction juridictionnelle (2014)
If the development of piracy off Somalia’s coasts seems now under control, pirates have moved and now concentrate their attacks in West Africa waters. To bring captured pirates to justice, the international community has relied on the courts of the states of the region, while requiring them to respect the standards of fair trial and the human rights. Strong supports, technical, financial and legal, have then been offered to them to improve their capacity of action. As the results were not immediate, the idea of creating an international court for the judgment of pirates, or an internationalized Court, has been discussed in the UN Security Council. It was ultimately rejected in favour of a reinforced international policy aiming at strengthening the action of national judicial processes against piracy.